Reusable Hydrogels Based on Lignosulfonate and Cationic Polymer for the Removal of Cr(Vi) from Wastewater - Sanchez-Poblete, J; Roa-Ruiz, K; Oyarce-Riveros, E; Boulett-Neira, A; Boulett-Neira, A (Elsevier B.V., 2023)
In this investigation, absorbent materials based on the polymer poly ([2-(acryloyloxy)ethyl]trimethylammonium chloride) were synthesized by radical polymerization using varying amounts of sodium lignosulfonate (LS) (0.00–30.0 wt%). The chemical composition was corroborated by Fourier transform infrared spectroscopy, and thermogravimetric analysis showed an increase in the thermal stability of the materials with the incorporation of LS. A porous surface with grooves was observed by scanning electron microscopy. In addition, the hydration in water and the removal capacity of hexavalent chromium (Cr(VI)) were tested by evaluating different experimental parameters. A hydration capacity of over 2000% was obtained when the incorporated percentage of LS exceeded 20.0 wt%. A maximum Cr(VI) removal efficiency of 88.4% was obtained by the adsorbent prepared with 5.00 wt% LS. The obtained results were well fit by a pseudosecond-order kinetic model and the Langmuir isotherm model. The presence of chromium on the surfaces of the adsorbents was corroborated. It was also found that the presence of interfering species led to a decrease of up to 11.0% of the maximum retention of Cr(VI) and that the materials could be reused up to five times without a significant decrease in efficiency. The adsorbent material prepared in this research has promising properties for application in the removal of metal anions, which could be extended to various anionic pollutants present in wastewater. © 2022 Elsevier B.V.